IMPLEMENTING TASK-BASED LANGUAGE TEACHING (TBLT) TO ENHANCE STUDENTS' SPEAKING, WRITING AND READING SKILLS: IS IT POSSIBLE? - Khairul Azmy; Dodi Widia Nanda (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2024)
Task-based language teaching (TBLT is a recently developed approach that has received significant attention from researchers in recent years. In this paper, TBLT refers to an approach that defines the use of tasks in various classroom activities in order to develop students' language skills. It is believed that TBLT offers different advantages in improving English skills, particularly by involving students in speaking activities in the classroom and enhancing their communication abilities. Given the considerable amount of research focused on applying TBLT in speaking activities, it prompts the question of whether it can also improve other skills, such as writing and reading. Therefore, the article examines its usefulness and explores the use of TBLT for improving and enhancing language skills in three separate areas: speaking, writing, and reading. The results show that, with proper and thorough task development settings, it can be suggested that TBLT can effectively be implemented to increase students' ability to communicate, reinforce their writing performance, and develop their reading comprehension skills. In this essence, TBLT emphasizes activities that focus on the learner and enables teachers to provide guidance as facilitators and supervisors. During the exercise and activities, students also have a chance to participate in tasks organically as authentic learning experiences. While there are criticisms and concerns about using TBLT, researchers have recognized these challenges and contend they can be effectively resolved. Ultimately, the findings of this paper have provided novel viewpoints on the implementation of TBLT in various aspects of language learning, which can be a valuable approach for improving students' English proficiency.